Russia and Africa: the Invasion of Ukraine Leads to the Next Major Crisis (The Strategic Review for Southern Africa, 2022)
Everything that was true until recently is no longer valid. Russia’s war against Ukraine has consequences for the entire world. In particular, low-income countries and countries that need to import food and energy have been plunged into crisis. Food, oil and gas exporters, on the other hand, benefit. African countries are experiencing the negative effects even more than other regions of the world. Following the consequences of the pandemic and the climate crisis, Africa is once again being dragged into an externally induced crisis, with hunger and poverty continuing to rise.